"Porque nós não temos fala" : um estudo sobre a organização política de CEMQS : Coordenação Estadual do Movimento Quilombola de Sergipe - Ribeiro, Ruth Paes (2015)
This dissertation describes the actions of a group of quilombola leaders in the state of Sergipe, in brazilian northeast. Through ethnographic inserts in the events and situations as well as in the spaces of monthly meetings to organize the "State Coordination of Quilombola Movement" is observed to (pre)existence and (re)formation of a network of actors, agencies and "things" around the public policy toward the called quilombolas in the state. The view of the network through the events allows us to notice a ensemble of interests, obligations and practices that explain discrepancies of power. The research show that the integration of quilombola people in the disp ute spaces for social rights, it boosts the difficult task of "organizing themselves politically" where the quilombola identity acts as reorganizing element in the space where they circulate. As it happens, the chain of complex relationships which they are made to act since the identity assumption – with ONGS, government agencies, political parties, documents, part of the Catholic Church, social movements, symbols, resources, etc. - Is modified according as relationship with each actor-network or which it represents, is now (re)discussed and estranged in the Quilombolas groups that have been investigated. The background of work indicate that the competency of social rights in public policy format to the quilombola people in the state of Sergipe not find its effectiveness in an ethnic legitimacy, but through an organization "Among themselves" and parallel linkage with the national quilombola network are urged to negotiate.